2015
DOI: 10.1089/rej.2014.1616
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in the Effects of the Apolipoprotein E Polymorphism on Risks of Diseases of the Heart, Cancer, and Neurodegenerative Disorders: Insights on Mechanisms from the Long Life Family Study

Abstract: The lack of evolutionary established mechanisms linking genes to age-related traits makes the problem of genetic susceptibility to health span inherently complex. One complicating factor is genetic trade-off. Here we focused on long-living participants of the Long Life Family Study (LLFS), their offspring, and spouses to: (1) Elucidate whether trade-offs in the effect of the apolipoprotein E e4 allele documented in the Framingham Heart Study (FHS) are a more general phenomenon, and (2) explore potential mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Numerous loci have been identified to show association across distinct diseases such as immune-related disorders, cancer and NDs, highlighting the common underlying biological pathways in the etiology of these complex diseases (Sivakumaran et al, 2011 ). For example, variants in APOE significantly associated with longevity and lifespan also confer risk of CVDs, AD and cancer (Ewbank, 2002 ; Christensen et al, 2006 ; Brooks-Wilson, 2013 ; Kulminski et al, 2014 , 2015a ). A putative loss of function variant in PTPN22 has been found to reduce the risk of Crohn's disease but to increase the risk of rheumatoid arthritis and DM (Plenge et al, 2005 ; Todd et al, 2007 ; Barrett et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous loci have been identified to show association across distinct diseases such as immune-related disorders, cancer and NDs, highlighting the common underlying biological pathways in the etiology of these complex diseases (Sivakumaran et al, 2011 ). For example, variants in APOE significantly associated with longevity and lifespan also confer risk of CVDs, AD and cancer (Ewbank, 2002 ; Christensen et al, 2006 ; Brooks-Wilson, 2013 ; Kulminski et al, 2014 , 2015a ). A putative loss of function variant in PTPN22 has been found to reduce the risk of Crohn's disease but to increase the risk of rheumatoid arthritis and DM (Plenge et al, 2005 ; Todd et al, 2007 ; Barrett et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common alleles of ApoE gene are E2, E3, E4, and there are 6 different ApoE phenotypes in the population: E2/E2, E2/E3, E2/E4, E3/E3, E3/E4, E4/E4, among which E3/E3 is the most common phenotype [15]. Studies at home and abroad have shown that ApoE gene polymorphism conform to the laws of genetics, but there are certain ethnic and regional differences, and there are differences in susceptibility to cardio-cerebrovascular diseases among ApoE individuals with different genotypes [16,17]. Results from previous studies suggest that ApoE E4 allele has a variable signi cance in terms of predicting the risk of vascular events in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…A functional promoter polymorphism in this gene shows an inverse genotypic association with risk of AD compared with cancer [ 320 , 321 ], with increased gene expression in cancer and decreases in AD. Similarly, the APOE4 allele, which represents a strong risk factor for AD, shows evidence of negative association with risk of cancer [ 324 ]. The tumor-suppressor gene TP53 , which directly controls tradeoffs between apoptosis, cellular senescence and cancer [ 329 , 351 ], is deleted or downregulated in most cancers, but demonstrates increased expression in brains of subjects with AD [ 328 , 352 ].…”
Section: Cancer Versus Neurodegenerative Diseasesmentioning
confidence: 99%